Socio-demographic Determinants of Caesarean Section Deliveries in India: Descriptive analysis of Cross-sectional data from National Family Health Survey - Thatkar, Pandurang Vithal; Bawa, Mukesh Suresh; Pandve, Harshal Tukaram; Desale, Atul Vilas; Chavan, Rahul Bhagchand (Indian Journal of Community Health, 2024)
Background: Increase in global rate of Caesarean deliveries poses significant public health concerns as it is associated with high costs and risks for maternal, new born health. In India understanding determinants of Caesarean deliveries is of paramount importance in order to prevent maternal and child health morbidity and mortality. Aims and Objective: To investigate the socio-demographic determinants of Caesarean deliveries in India using cross-sectional data from National Family Health Survey. Methodology: The present study is a cross-sectional record based study using data from National Family Health Survey conducted in India between 2019 and 2021. The primary outcome variable is Caesarean delivery, while predictors are socio-demographic and obstetric factors. Frequency analysis used for socio-demographic variables and binary logistic regression was used to determine the determinants of Caesarean deliveries among women in the reproductive age group. The analysis was done using IBM SPSS Statistics 26.0 Software. Results: The socio-demographic and obstetric factors like maternal age, residence, education, employment, BMI, Birth order, number of Antenatal visits, place of delivery, wealth index, and media exposure are associated with Caesarean delivery. Conclusions: The study provides insights into the factors influencing Caesarean deliveries rates among women in India.